The evaluative dimension of metaphor in discourse: Nn the possibilities of bringing together conceptual metaphor theory and appraisal theory - Bogetić Ksenija D. (Južnoslovenski Filolog, 2020)
The mechanisms of metaphorical evaluation have to date been little explored in the study of evaluative language and the study of metaphor, despite some earlier attempts to place them more firmly on the linguistic science agenda. The founders of Conceptual Metaphor Theory have argued that metaphor structures thought by influencing not only our understanding of concepts, but also our ability of criticising, evaluating and stance taking (Lakoff, Johnson 1999: 2), which is sporadically mentioned in approaches to linguistic evaluation, but with no theoretical or practical interaction with existing analyses of metaphor in discourse. The present paper explores the nature of metaphorical evaluation, drawing on the example of metaphorical representations of language in newspaper discourse. The analysis of the discourse on language is used to discuss metaphorical evaluation, to empirically examine its prominence in the discourse, and its contribution to the construction of meaning, as well as to discuss the broader theoretical and methodological implications. The findings point to the importance of metaphor in the evaluative subsystem of graduation, seen in the interaction of metaphorical and hyperbolic meanings. More broadly, it is argued that bringing together conceptual metaphor analysis and Appraisal Theory analysis offers a rich theoretical apparatus for socio-cognitive discourse analysis.